Taḥlīlu al Akhṭa’i al Imlā’iyyati fī Kitābati al Lughati al ‘Arabiyyati ‘inda al Talāmīżi fī al Madrasati Ahmad Daḥlān fī Madīnati Jāmbi (Dirāsatun Taḥlīliyyatun fī Qawā’idi al Imlā’iyyati) - Putri, Nurhaliza; Nurlaily, Nurlaily (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2022)
The type of research used is qualitative research. Research whose data is obtained using learning methods in the field or personal fieldwork. This study analyzes writing errors in writing Arabic at Madrasah Tsanawiyah Ahmad Dahlan in Jambi City. This research was conducted because the researchers found the problem of students' writing errors in spelling in Arabic at Madrasah Tsanawiyah in Ahmad Dahlan, Jambi City. at Ahmad Dahlan, Jambi City. 2. What are the causes of frequent errors in writing spelling in Arabic at Madrasah Tsanawiyah in Ahmad Dahlan, Jambi City.3. What is the solution to overcome spelling errors in writing Arabic for students at Madrasah Tsanawiyah in Ahmad Dahlan, Jambi City. The results of the study show that: The causes of imla errors after using the theory that there are errors made by students at the Ahmad Dahlan School in the city of Jambi include: errors in terms of writing with different amounts in each surah including errors in writing surah alfatihah, errors in surah an-nas, Error in surah al-Maun. as well as errors in hamzah washol and hamzah qhot'i and errors in writing Arabic. the causes of student errors are lack of understanding of Arabic vocabulary, lack of understanding of recitation and do not understand writing hijaiyah letters, do not understand the rules, lack of practice on imla and lack of focus in learning imla. The solution to reducing imla errors is by: 1.The teacher's role The teacher pays more attention to imla errors and provides training in Arabic writing, coupled with an understanding of Arabic vocabulary, 2. emphasizes understanding related to recitation and also in writing hijaiyah letters so that students are more it's easy to write IMLA, 3. provide practice or learning related to IMLA, and use books related to Islamic imla learning. The school supports it by providing facilities for books related to IMLA to make it easier for students to understand what IMLA and Qawaidul Imla are so that students more interested and enthusiastic in learning Arabic.